Multihop Self-Calibration Algorithm for Ultra-Wideband (UWB) Anchor Node Positioning - Herbruggen, Ben Van; Luchie, Stijn; Fontaine, Jaron; De Poorter, Eli (IEEE journal of indoor and seamless positioning and navigation., 2023)
Ultra-wideband (UWB) is an emerging technology for indoor localization systems with high accuracy and excellent resilience against multipath fading and interference from other technologies. However, UWB localization systems require the installation of infrastructure devices (anchor nodes) with known positions to serve as reference points. These coordinates are of utmost importance for the performance of the indoor localization system as the position of the mobile tag(s) will be calculated based on this information. Currently most large-scale systems require manual measurement of the anchor coordinates, which is a time-consuming and error-prone process. Therefore, we propose an algorithmic approach whereby based on measurements of the position of a small random chosen subset of anchors, the position of all other anchors is calculated automatically by collecting distances between all anchors with two-way-ranging UWB. In this article we present a three stage algorithm which contains: 1) an initialization phase; 2) a global optimization phase; and 3) an optional extra calibration phase with a mobile node. In contrast to related work, our approach also works in multihop environments with severe non-line-of-sight effects. In a real world multihop Industry 4.0 environment with metal racks as obstacles and 18 UWB nodes, the algorithm is able to localize the anchors with an mean absolute error of only 21.6 cm.